1985
DOI: 10.3171/jns.1985.63.4.0617
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain metabolite levels following mild experimental head injury in the cat

Abstract: Glucose, adenosine triphosphate, phosphocreatine, and lactate levels in the cortex, striatum, diencephalon, hippocampus, cerebellum, and brain stem were measured in cats 1 hour after they were subjected to low-level (2 atm) fluid-percussion injury. Following injury, there was a mild but significant increase in lactate levels in the majority of regions studied. The hippocampus exhibited the highest percentage increase in lactate (fourfold). The cortical area directly under the trauma device showed a threefold l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…Damage or elimination of mitochondrial populations after injury may underlie the sustained hypometabolic state reported to be initiated within hours after experimental TBI (Vink et al, 1988;Yoshino et al, 1991;Ginsberg et al, 1997;Moore et al, 2000) that is coupled to increased brain lactate concentration (Nilsson et al, 1990;Kawamata et al, 1995) and reduced cerebral blood flow (Yamakami and McIntosh, 1991;Ginsberg et al, 1997), suggesting that cerebral metabolism may shift towards anaerobic glycolysis. The acute decrease in the [ATP]/[ADP][P i ] ratio that arises from increases in cytosolic ADP (Vink et al, 1988;Headrick et al, 1994) and reductions in tissue ATP concentrations (Signoretti et al, 2001) (Table 1) incorporates both a loss of energy production and an increase in energy demand after moderate, but not mild (Yang et al, 1985), brain injury. Cerebral metabolic alterations and mitochondrial damage may contribute to the progressive cell death observed in the parietotemporal cortex and CA3 region of the hippocampus after FP brain injury (Hicks et al, 1996;Smith et al, 1997) that would be accompanied by additional loss of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Damage or elimination of mitochondrial populations after injury may underlie the sustained hypometabolic state reported to be initiated within hours after experimental TBI (Vink et al, 1988;Yoshino et al, 1991;Ginsberg et al, 1997;Moore et al, 2000) that is coupled to increased brain lactate concentration (Nilsson et al, 1990;Kawamata et al, 1995) and reduced cerebral blood flow (Yamakami and McIntosh, 1991;Ginsberg et al, 1997), suggesting that cerebral metabolism may shift towards anaerobic glycolysis. The acute decrease in the [ATP]/[ADP][P i ] ratio that arises from increases in cytosolic ADP (Vink et al, 1988;Headrick et al, 1994) and reductions in tissue ATP concentrations (Signoretti et al, 2001) (Table 1) incorporates both a loss of energy production and an increase in energy demand after moderate, but not mild (Yang et al, 1985), brain injury. Cerebral metabolic alterations and mitochondrial damage may contribute to the progressive cell death observed in the parietotemporal cortex and CA3 region of the hippocampus after FP brain injury (Hicks et al, 1996;Smith et al, 1997) that would be accompanied by additional loss of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Although, most of the TBI rats did not show significantly elevated Lac levels, one out of the eight rats exhibited a dramatic increase of Lac, coupled with a more severe drop in NAA and Glu although the conventional MRI showed similar levels of injury as that of other rats. While the discrepancy in this one rat is unclear, the presence of Lac has been related to multiple factors, including the increased energy demand to restore the ionic balance (Kawamata et al, 1995) and the disordered mitochondrial dysfunction (Ishige et al, 1988;Unterberg et al, 1988;Yang et al, 1985) at the initial stage of the injury. Future studies with histological verification will need to be performed in order to understand the subtle changes that may be responsible for the ischemic conditions far from the injury, as evidenced from increased lactate from the hippocampus and the thalamic region.…”
Section: Xu Et Almentioning
confidence: 99%
“…The biochemical and cellular changes in neurons and glia after TBI are complex and dynamic. The pathophysiology typically begins with mechanical trauma to the brain (the primary injury), followed rapidly by increased vascular permeability, altered ionic balance, oxidative stress, excitotoxic damage, inflammation, and mitochondrial dysfunction leading to further cell death and injury (secondary injury) (Hovda et al, 1991;Ishige et al, 1988;Kawamata et al, 1995;Lenzlinger et al, 2001;Morganti-Kossmann et al, 2002;Roberson et al, 2006Xiong et al, 1997Yang et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In the late 70s and 80s, electron microscopy studies confirmed that mitochondrial swelling was an integral part of the subcellular changes following brain injury, 28 and regional brain metabolite level alterations supported mitochondrial dysfunction in TBI. 29 Since then it became progressively clear that disruption of mitochondrial function might play a central role in the pathophysiology of secondary TBI. Mitochondria may act as Ca 2ϩ sinks that sequester Ca 2ϩ to preserve low cytoplasmic Ca 2ϩ concentrations.…”
Section: Mitochondriamentioning
confidence: 99%